The influence of women's fear, attitudes and beliefs of childbirth on mode and experience of birth - Haines Helen M; Rubertsson Christine; Pallant Julie F; Hildingsson Ingegerd (BMC, 2012)
Abstract Background Women's fears and attitudes to childbirth may influence the maternity care they receive and the outcomes of birth. This study aimed to develop profiles of women according to their attitudes regarding birth and their levels of childbirth related fear. The association of these profiles with mode and outcomes of birth was explored. Methods Prospective longitudinal cohort design with self report questionnaires containing a set of attitudinal statements regarding birth (Birth Attitudes Profile Scale) and a fear of birth scale (FOBS). Pregnant women responded at 18-20 weeks gestation and two months after birth from a regional area of Sweden (n = 386) and a regional area of Australia (n = 123). Cluster analysis was used to identify a set of profiles. Odds ratios (95% CI) were calculated, comparing cluster membership for country of care, pregnancy characteristics, birth experience and outcomes. Results Three clusters were identified - 'Self determiners' (clear attitudes about birth including seeing it as a natural process and no childbirth fear), 'Take it as it comes' (no fear of birth and low levels of agreement with any of the attitude statements) and 'Fearful' (afraid of birth, with concerns for the personal impact of birth including pain and control, safety concerns and low levels of agreement with attitudes relating to women's freedom of choice or birth as a natural process). At 18 -20 weeks gestation, when compared to the 'Self determiners', women in the 'Fearful' cluster were more likely to: prefer a caesarean (OR = 3.3 CI: 1.6-6.8), hold less than positive feelings about being pregnant (OR = 3.6 CI: 1.4-9.0), report less than positive feelings about the approaching birth (OR = 7.2 CI: 4.4-12.0) and less than positive feelings about the first weeks with a newborn (OR = 2.0 CI 1.2-3.6). At two months post partum the 'Fearful' cluster had a greater likelihood of having had an elective caesarean (OR = 5.4 CI 2.1-14.2); they were more likely to have had an epidural if they laboured (OR = 1.9 CI 1.1-3.2) and to experience their labour pain as more intense than women in the other clusters. The 'Fearful' cluster were more likely to report a negative experience of birth (OR = 1.7 CI 1.02- 2.9). The 'Take it as it comes' cluster had a higher likelihood of an elective caesarean (OR 3.0 CI 1.1-8.0). Conclusions In this study three clusters of women were identified. Belonging to the 'Fearful' cluster had a negative effect on women's emotional health during pregnancy and increased the likelihood of a negative birth experience. Both women in the 'Take it as it comes' and the 'Fearful' cluster had higher odds of having an elective caesarean compared to women in the 'Self determiners'. Understanding women's attitudes and level of fear may help midwives and doctors to tailor their interactions with women.